Grundtvigs gudstjenestesyn liturgisk - Rønkilde, Jette Bendixen (Grundtvig-studier, 2015)
A Liturgical Theological Re-reading of Grundtvig’s View on Worship Through a description of well-known works by Grundtvig, the article examineshow Grundtvig’s view on worship can be said to form an independentliturgical theological position, which the author characterizes asa theory of communication of worship. The examination takes the Anglo-American theory of worship, Liturgical Theology, as its starting point.Then, Grundtvig’s view on worship is reinterpreted against main currentsand main issues of contemporary Liturgical Theology. The article demonstrateshow structures in the works of Grundtvig and in liturgical theologyparallel each other, an observation that frames Grundtvig as a protoliturgical theologian. Grundtvig’s specific liturgical theological positionis firmly rooted in a trinitarian understanding of worship as a meetingplace between God and human beings and the experience of worship asintrinsically bound to aesthetic experience. Grundtvig’s view of worshipcan therefore be deemed to be in keeping with an aesthetic Trinitarianview that significantly emphasizes the third article of faith in the patristicsymbols and the practice of the assembly.